Serious Game Design Of Sound Identification For Deaf Children Using The User Centered Design - Fadmi Rina; Anis Susila Abadi; Sholeh Huda (Telematika, 2022)
The loss of hearing function in deaf children causes deaf children to experience obstacles in listening to the sound of objects or sounds of language as children generally hear. Therefore, it is necessary to optimize the hearing function of deaf children. The Development of Sound and Rhythm Perception Communication (PKPBI) is a special program to practice understanding sound so that the remaining hearing of deaf children can be maximized. So far, the PKPBI learning media at the sound identification stage used by the Karnna Manohara Yogyakarta Special School teacher is the keyboard. However, the keyboard has weaknesses such as the collection of sounds on the keyboard is very limited. Another problem is the Covid 19 pandemic, PKPBI learning is less than optimal due to limited face-to-face meetings. The purpose of this research is to design a serious game as a learning medium for sound identification for deaf children that can be used in the classroom and at home. The method used to design serious sound identification games is User Centered Design (UCD). Based on the research results, the design of this serious game can be developed into a serious game application to practice sound identification in deaf children.